Structure and Relationships of University Instructors’ Achievement Goals - Daumiller, Martin; Grassinger, Robert; Dickhäuser, Oliver; Dresel, Markus (Frontiers in Psychology, 2016)
The present study examines the achievement goals of university instructors, particularly the structure of such goals, and their relationship to biographic characteristics, other aspects of instructors’ motivation, and teaching quality. Two hundred and fifty-one university instructors (184 without PhD, 97 with PhD, thereof 51 full professors; 146 males, 92 females) answered a questionnaire measuring achievement goals, self-efficacy, and enthusiasm in altogether 392 courses. Teaching quality was assessed using reports from 9,241 students who were attending these courses. Confirmatory factor analyses revealed mastery, performance approach, performance avoidance, work avoidance, and relational goals as being distinguishable from each other. Distinct relationships were found between different instructors’ achievement goals, and gender, age, and career status as well as self-efficacy and enthusiasm. Hierarchical linear models suggested positive associations of instructors’ mastery goals with teaching quality, while negative associations were indicated for performance avoidance goals and work avoidance goals in relation to teaching quality. Exploratory analyses conducted due to a quite large correlation between performance approach and performance avoidance goals indicated that for university instructors, differentiating performance goals into appearance and normative components might also be adequate. All in all, the study highlights the auspiciousness of the theoretical concept of university instructors’ achievement goals and contributes to making it comprehensively accessible.